ON THE CLASSIFICATION OF THE GORGONOPSIA - Sigogneau, D. (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 1968)
The work here summarized represents an attempt to review the South African Gorgonopsians, an attempt based on a re-examination of the cranial anatomy of the type material and a comparison of all the specimens available. The possible origin of the group from the Russian eotheriodonts is discussed in conclusion.